PEMAHAMAN MASYARAKAT DESA MARENGAN LAOK SUMENEP TERKAIT MAKANAN SEHAT DAN HALAL - Nuniek Herdyastuti (Universitas Negeri Surabaya, 2020)
The majority of the population in Indonesia is Muslim, so a halal food guarantee is needed. In addition toconsuming healthy food, it is better for the community now to start getting used to implementing halal food.Halal food is essentially food that is obtained and processed in the right way according to religion. Whilegood food can be considered with reasonable and health measures. The purpose of this activity is toincrease community understanding, especially in Marengan Laok village, regarding halal products and safeadditives and their effects on health. The training is carried out by way of socializing and counselinghealthy and halal food. The results obtained were an increase in the understanding of the participants ofthe training on halal and healthy products as well as being able to identify food grade materials and theofficial halal logo from the MUI. The response of participants to this activity was very good based on thequestionnaire responses given.